2011
DOI: 10.1016/j.jim.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Antigen profiles for the quantitative assessment of eosinophils in mouse tissues by flow cytometry

Abstract: Much of our current understanding of eosinophil-associated pathologies has developed from the use of mouse models. While mouse eosinophils can be readily detected by flow cytometric methods, most studies do not document the efficiency of this process compared to direct counting of stained cells. Our intent was to address this knowledge gap by identifying one or more eosinophil-specific antigen profiles that yielded flow cytometric data that was statistically consistent with direct counts. We found that anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
(27 reference statements)
6
36
0
Order By: Relevance
“…Siglec-F was also found to be expressed by AMs, a finding consistent with that of previous studies (28,29), and by lung neutrophils, which has not been reported before. Although CD125 expression is thought to be restricted to eosinophils and B-1 cells in mice (28,29,(62)(63)(64), we unexpectedly found that lung neutrophils expressed high levels of CD125, suggesting that these cells may also be influenced by IL-5. Supporting this finding, mouse neutrophils have been shown to migrate in response to rIL-5 treatment (65).…”
Section: Discussionsupporting
confidence: 92%
“…Siglec-F was also found to be expressed by AMs, a finding consistent with that of previous studies (28,29), and by lung neutrophils, which has not been reported before. Although CD125 expression is thought to be restricted to eosinophils and B-1 cells in mice (28,29,(62)(63)(64), we unexpectedly found that lung neutrophils expressed high levels of CD125, suggesting that these cells may also be influenced by IL-5. Supporting this finding, mouse neutrophils have been shown to migrate in response to rIL-5 treatment (65).…”
Section: Discussionsupporting
confidence: 92%
“…3A, 3B). Interestingly, strict gating based on the FMO controls incorporated a range of Siglec-F expressing cells and higher overall percentages than have been previously reported for mature eosinophils (25). To further examine eosinophil related populations within this Siglec-F + pool, we defined a population of GMP-like cells (Lin − Sca1 − Siglec-F + IL-5Rα − SSC lo ckit hi CD34 + ST2 + ), eosinophil precursors (EoPre) (Lin hi Sca1 − Siglec-F lo IL-5Rα + SSC lo ckit − CD34 − ST2 − ), and EoM cells (Lin lo Sca1 − Siglec-F hi IL-5Rα + SSC hi ckit − CD34 − ST2 lo ) (characterization and FMO control staining shown in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Spleen cell suspensions in HBSS supplemented with 1% FBS and 10 mM HEPES were prepared as described (Dyer et al , 2011). Red blood cells were lysed with ACK lysing buffer (Lonza).…”
Section: Methodsmentioning
confidence: 99%